2017
DOI: 10.1521/pedi_2017_31_273
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Threat Sensitivity in Borderline Personality Disorder: An Eye-Tracking Study

Abstract: Threat sensitivity is a prominent predictor of interpersonal dysfunctions in borderline personality disorder (BPD), leading to intense, aversive feelings of threat and eventually dysfunctional behaviors, such as aggression. In the present study, BPD patients and healthy volunteers classified angry, fearful, neutral, and happy faces presented for 150 ms or 5,000 ms to investigate initial saccades and facial scanning. Patients more often wrongly identified anger, responded slower to all faces, and made faster sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
61
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 49 publications
11
61
0
4
Order By: Relevance
“…In line with the expected deficits in cognitive control of emotional action tendencies and previous findings in angerprone or aggressive individuals, [38][39][40] patients with BPD showed relatively faster approach than avoidance responses to angry faces. Our data add to previous reports of an increased likelihood to detect subtle signals of facial anger, 41,42 a stronger initial orientation toward negative emotional faces, 43 and an increased percentage of attention shifts toward threatening emotional faces 44,45 in patients with BPD. Together these studies suggest a hypersensitivity for negative or threatening emotional information as well as difficulties in the control of emotional impulses -2 symptoms that we have recently proposed as possible mechanisms for the increased tendency to act out aggressively in response to interpersonal threats or provocations.…”
Section: Discussionsupporting
confidence: 85%
“…In line with the expected deficits in cognitive control of emotional action tendencies and previous findings in angerprone or aggressive individuals, [38][39][40] patients with BPD showed relatively faster approach than avoidance responses to angry faces. Our data add to previous reports of an increased likelihood to detect subtle signals of facial anger, 41,42 a stronger initial orientation toward negative emotional faces, 43 and an increased percentage of attention shifts toward threatening emotional faces 44,45 in patients with BPD. Together these studies suggest a hypersensitivity for negative or threatening emotional information as well as difficulties in the control of emotional impulses -2 symptoms that we have recently proposed as possible mechanisms for the increased tendency to act out aggressively in response to interpersonal threats or provocations.…”
Section: Discussionsupporting
confidence: 85%
“…Our first finding of faster reaction times to angry compared with happy faces is in line with the theory that patients with BPD show a bias toward threatening information (4). For example, patients with BPD show faster initial saccades into the eyes of angry faces, (7) are more likely to recognize even subtle signals of anger in facial stimuli (5), and misconstrue happy, fearful, or neutral faces more often as angry (6). In the healthy participants though, positive stimuli triggered faster emotional reactions than negative stimuli, replicating previous findings (39).…”
Section: Discussionsupporting
confidence: 81%
“…A related aspect is hypersensitivity to threatening information when processing emotional states of others (4). Patients with BPD tend to detect subtle signals of threat and to focus their attention on threatening interpersonal cues (4)(5)(6). Furthermore, faster initial saccades into the eyes-the most threatening part-of angry faces in patients with BPD suggest approach rather than avoidance behavior to interpersonal threat cues (7).…”
Section: Introductionmentioning
confidence: 99%
“…A more negative processing of neutral, ambiguous, or positive emotional faces was also reported in several other recent studies with relatively large groups of female BPD patients and matched healthy control groups (e.g., Catalan et al [9], Daros et al [10], Izurieta Hidalgo et al [11], Thome et al [12], and van Dijke et al [13]; however, see Lowyck et al [14] where now alterations could be found). Confirmation for a threat hypersensitivity also comes from recent eye-tracking studies, which showed faster and more initial eye movements towards the eyes of angry faces and an inability to disengage attention from fearful eyes in BPD patients [15, 16]. …”
Section: Recent Behavioral Findingsmentioning
confidence: 97%
“…Several further studies have included trait measures, such as aggressiveness [16], impulsivity, or effortful control [30] and found that these aspects might explain further variance besides general BPD symptomatology. Moving to a more dimensional approach, the investigation of associations between specific behavioral tendencies and emotion processing deficits will become more and more important.…”
Section: Recent Behavioral Findingsmentioning
confidence: 99%